النظام القانوني لاستغلال الاراضي الصحراوية في جمال الفلاحةالاستراتيجية - لامية تابعي; رزان هادفي (جامعة الوادي University of El Oued, 2025)
تهدف هذه الدراسة إلى إبراز دور قطاع الفلاحة في تحقيق الأمن الغذائي وتنويع المحاصيل لتقليل التبعية للاستيراد، لا سيما في المحاصيل الاستراتيجية. وتسلط الضوء على توجه الدولة نحو ترقية الاستثمار الفلاحي عبر دمج القطاعين الصناعي والفلاحي ضمن سلسلة زراعية متكاملة تعتمد على الإنتاج بمعايير عالمية في المناطق الصحراوية. كما تركز الدراسة على أهمية الصناعات التحويلية، ومعالجة مشكلات التخزين والنقل، والتكامل بين الإنتاج النباتي والحيواني. وقد خلصت الدراسة إلى أن هذا التوجه مدعوم بنصوص قانونية جديدة استحدثت لتنظيم وتنمية الزراعة الاستراتيجية في الأراضي الصحراوية بما يضمن ديمومة واستدامة القطاع. This study aims to highlight the role of the agricultural sector in achieving food security and diversifying crops to reduce import dependency, particularly regarding strategic crops. It examines the shift toward promoting agricultural investment by integrating the industrial and agricultural sectors within an integrated agricultural chain that adheres to international production standards in desert regions. The study also addresses the importance of manufacturing industries, resolving storage and transport issues, and integrating livestock farming with strategic crop production. It concludes that this strategic direction is reinforced by new legal frameworks designed to regulate and develop strategic agriculture in Saharan lands, ensuring sector sustainability and efficiency
قانون عقاري
Keywords: الأمن الغذائي، الاستثمار الفلاحي، الزراعة الاستراتيجية، الصناعات التحويلية، المناطق الصحراوية، السلسلة الزراعية المتكاملة.; Food Security; Agricultural Investment; Strategic Agriculture; Manufacturing Industries; Desert Regions; Integrated Agricultural Chain.